Life and work strategies of pensioners in contemporary Russia - S. A. Barkov; A. V. Markeeva; I. V. Kolodeznikova (RUDN journal of Sociology, 2022)
Based on the data of the All-Russian survey of pensioners (February 2022), the article reveals their opinions on working in retirement, reasons for continuing work, problems when changing jobs, attitudes to new forms of employment, and life priorities. The article continues the analysis presented in the article “Employment of the elderly: Social imperatives and barriers in contemporary Russia” (2022; 22 (1)). The most important factor affecting the life strategies of the elderly in the post-industrial society is their increasing involvement in labor activity. The survey showed that the basic incentive for working in the older age is additional income. In depressed regions and during crises, work is one of the possible means for survival of both pensioners and their families. However, under the growing well-being of working pensioners, social motives and incentives for self-realization become fundamentally important. Differences in the pensioners’ motivation to continue their labor activity are determined by both personal characteristics (gender, age) and local social-economic circumstances (place of residence). Thus, Moscow pensioners, who get city allowances and feel less poor than pensioners in other regions, express special opinions on a number of issues. Life strategies differ significantly by gender: retired women are less satisfied with their status as non-working pensioners and are more willing to use new forms of employment, which may lead to more active employment of women in the future. More than a third of pensioners, contrary to stereotypes, are ready to work remotely. Most pensioners are not ready to become selfemployed, but many start to consider this form of employment and admit its benefits. To improve their social role, pensioners propose to develop volunteer and educational projects in which they could share knowledge and experience with the younger generations, and to hold events that would show the elderly’s contribution to the development of society.